Relationship with creativity: Employees working in vocational schools of Qadisiyah Governorate - Mhemed, Wedad. M. (Opción, 2020)
This study aimed to investigate the impact of conflict in organization on creativity. There is a significant inconclusive and elusive literature to explain the relationship of conflict with creativity. The instrument was divided into three parts named as task conflict, Interrelation conflict and creativity. It is found that interrelation conflict has a linear and negative effect on creativity while task conflict has curvilinear relationship with creativity. This study recommends managers and supervisors who to control task conflict at moderate level by facilitating communication channels. The benefits of task conflict can be collected when it is at moderate or low level.